2021
DOI: 10.1186/s12969-021-00646-7
|View full text |Cite
|
Sign up to set email alerts
|

Home-based exercise program for adolescents with juvenile dermatomyositis quarantined during COVID-19 pandemic: a mixed methods study

Abstract: Background Exercise has been suggested to prevent deterioration of health-related quality of life (HRQL) and overall health in pediatric rheumatologic diseases during the COVID-19 pandemic. Herein we describe the effects of a 12-week, home-based, exercise program on overall health and quality of life among quarantined patients with juvenile dermatomyositis (JDM). Method This prospective, quasi-experimental, mixed methods (qualitative and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Astley and colleagues' 20 study found no change in SDQ scores or Emotional Functioning scale in the PedsQL, whilst Wong and colleagues 23 reported significantly decreased SDQ scores in the intervention group. Furthermore, the remaining three studies that looked at anxiety‐related measures all reported results favoring the intervention.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Astley and colleagues' 20 study found no change in SDQ scores or Emotional Functioning scale in the PedsQL, whilst Wong and colleagues 23 reported significantly decreased SDQ scores in the intervention group. Furthermore, the remaining three studies that looked at anxiety‐related measures all reported results favoring the intervention.…”
Section: Resultsmentioning
confidence: 95%
“…Five of the nine identified articles involved live online exercise programs or pre‐recorded videos that were accessible online or through apps 15–17,20,23 . Four of these were conducted during home schooling or lockdowns due to the COVID‐19 pandemic, whilst the study by Wong et al 23 aimed to increase physical activity in children and adolescents using a mobile app, pre‐pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…It was feasible for one coach to lead several athletes. In addition, we were not limited by the physical distances of where athletes and coaches were located and athletes could participate from their own home, which lead to high convenience as has been shown in other studies (Rowland et al, 2016 ; Astley et al, 2021 ; Calcaterra et al, 2021 ; Weiss et al, 2021 ). However, it was difficult at times to fully engage remote athletes in a way that was both safe and challenging without anyone close by to supervise for their specific movement challenges.…”
Section: Discussionmentioning
confidence: 98%
“…Another advantage of this study was the prompt access to a pediatric multidisciplinary team, especially for adolescents with physical and mental impacts, such as pediatric psychiatrists or psychologists, nurses, nutritionists, social workers, and physical educators. 16 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%